Addressing COVID-19 Communication and Management by a Systems Thinking Approach - Gonella, Francesco; Casazza, Marco; Cristiano, Silvio; Romano, Alessandra (Frontiers in Communication, 2020)
A systemic stock-flow diagram is proposed for the communication and the management of health services and strategies concerning the COVID-19 epidemic. The possible role of government interventions in activating systemic leverage points is also addressed. The presented approach, based on Systems Thinking, can create the basis for creating an analytical simulator of the disease spreading, and at the same time the diagram can constitute a powerful tool for improving the quality of information to both policy-makers and general public in situations of epidemic.